Protection of Carbonyl Groups as 2,4-Dinitro-phenylhydrazone Catalyzed by Silica Sulfuric Acid - Reza Kiasat, Ali; Kazemi, Foad; Fallah Mehrjardi, Mehdi (Asian Journal of Chemistry, 2010)
The protection of aldehydes and ketones as 2,4-dinitrophenylhydrazone is studied using silica sulfuric acid as solid acid catalyst. The reaction is clean and work-up is very simple. The use of this solid acid catalyst allows replacing the usual soluble inorganic acid, contributing to waste reduction.